Analisis Efektivitas Dan Kontribusi Penerimaan Pajak Bumi Dan Bangunan (PBB) Terhadap Pendapatan Asli Daerah Di Kota Metro Tahun 2017-2021 - Kamala, Shafa Tasya; Hendri, Nedi; Rahayu, Sri Retnaning (Expensive: Jurnal Akuntansi dan Keuangan, 2023)
This study aims to determine the level of effectiveness and contribution of land and building tax revenue to the regional revenue of Metro City in 2017-2021. The method used in this research is a qualitative method with a descriptive approach. The data used in this study are secondary data, namely internal data provided by the Metro City Regional Tax and Retribution Management Agency and primary data obtained from direct observations and interviews with related parties. The results of the study show that the 2017-2021 Metro City land and building tax revenue is fluctuating. The level of effectiveness of land and building tax revenue is in the less effective category. And the contribution of land and building tax to regional own-source revenue is in the very less category.